ASTI data inform policies to improve agricultural research capacity, efficiency, and output delivery in Swaziland - CGIAR Research Program on Policies, Institutions, and Markets (2017)
ASTI data contributed to a policy that prioritized higher education training for agricultural researchers in Swaziland, and was used in presentations, posters, and meeting communications to advocate for a reform of the national agricultural research system which is expected to improve research funding, the recruitment and advancement of qualified researchers, and research output delivery.